Dexmedetomidine and Dexamethasone as Adjuvants to the Local Anesthetic Mixture in Rhomboid Intercostal and Sub-Serratus Block for Video-Assisted Thoracoscopic Surgery: A Randomized, Double-Blind, Controlled Trial - Liu QF; Shi CN; Tong JH; Li KP; Yang JJ; Ji MH; Liu QR (Dove Medical Press, 2024)
Quan-fang Liu,1 Cui-na Shi,1 Jian-hua Tong,1 Kun-peng Li,1 Jian-jun Yang,2 Mu-huo Ji,1 Qing-ren Liu3 1Department of Anesthesiology, The Second Affiliated Hospital of Nanjing Medical University, Nanjing, People's Republic of China; 2Department of Anesthesiology, Pain and Perioperative Medicine, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People's Republic of China; 3Department of Anesthesiology, Xishan People's Hospital of Wuxi City, Wuxi, People's Republic of ChinaCorrespondence: Qing-ren Liu, Department of Anesthesiology, Xishan People's Hospital of Wuxi City, Wuxi, People's Republic of China, Email liuqr5250@163.com Mu-huo Ji, Department of Anesthesiology, The Second Affiliated Hospital, Nanjing Medical University, Nanjing, People's Republic of China, Email jimuhuo2009@sina.comBackground: The utilization of adjuvants such as dexamethasone and dexmedetomidine in combination with local anesthetics has proven effective in extending analgesia duration. We aimed to investigate the potential efficacy of combining dexmedetomidine and dexamethasone in rhomboid intercostal and sub-serratus (RISS) block for prolonging postoperative analgesia in patients undergoing video-assisted thoracoscopic surgery (VATS).Methods: We did this randomized, double-blind, controlled trial in two tertiary-care hospitals. A total of eighty-eight patients undergoing VATS under general anesthesia were enrolled in this study. They were randomly assigned into four groups: ropivacaine (R) group, ropivacaine + dexmedetomidine (RM) group, ropivacaine + dexamethasone (RS) group, or ropivacaine + dexmedetomidine + dexamethasone (RSM) group. The primary outcome measure was the duration of analgesia. Secondary outcomes included Numeric Rating Scale (NRS) scores, cumulative oxycodone consumption, and adverse effects.Results: The RSM group exhibited a significantly prolonged duration of analgesia at 1073.5 min (932.0- 1283.3) compared to the R group with a duration of 154.5 min (80.5- 199.3) and the RS group with a duration of 282.0 min (195.3- 350.0, P < 0 0.001). The cumulative oxycodone consumption during the 0- 12 hours and 0- 24-hours period was significantly reduced in the RSM group compared to the R group (P < 0.05). There was also a lower incidence of nausea at 48 hours postoperatively in the RSM group compared to the RM group. However, there were no significant differences between the four groups regarding NRS pain scores.Conclusion: The combination of ropivacaine, dexmedetomidine, and dexamethasone in RISS block significantly prolongs the duration of postoperative analgesia following VATS.Keywords: nerve block, pain, postoperative, anesthesia, video-assisted thoracoscopic surgery